FACTORS THOSE ARE RELATED TO THE INCIDENCE OF NEEDLE STICKS ON INPATIENT NURSES AT DR. SITANALA KOTA TANGERANG HOSPITAL - Novia Chulayati (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Avoiding needles for a hospital nurse is very important because even the most minor treatment can pose a risk to the nurse. Use of personal protective equipment, age, years of service, knowledge of occupational health and safety, and training are related to needle sticking for hospital nurses. This research aims to analyze the relationship between the use of personal protective equipment, age, years of service, knowledge, and training with the incidence of needle sticking to nurses in hospitals. This type of research is observational with a cross-sectional study approach. The sample in this study was 47 people. Primary data collection using a questionnaire. Data analysis uses univariate statistics to describe the characteristics of respondents, and bivariate statistics use the Chi-Square test to analyze the relationship between variables. The study shows that there is a significant relationship between the use of Personal Protective Equipment, knowledge and training with the needle sticking in nurses at Dr. Sitanala Kota Tangerang Hospital, with the results of the analysis of Personal Protective Equipment (p = 0.043), knowledge (p = 0.035) and training (p = 0.024). There is no significant relationship between age and years of service with the needle sticking in nurses at Dr. Sitanala Kota Tangerang Hospital, with the analysis of age (p = 0.183) and years of service (p = 0.103). From the results of this study, it was suggested that it was necessary to increase knowledge and training for nurses and improve compliance in preventing needle sticks, both